2019
DOI: 10.4314/jasem.v23i3.26
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil metals status in parts of Rivers State, Nigeria

Abstract: The study evaluates levels of metals in soils of 9 locations in Port Harcourt and its environs in Rivers State in Nigeria. Composite samples were collected by random sampling from each of the 9 test locations, 3 control samples were also collected from each of the study areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
2
Order By: Relevance
“…The study by Wanjala et al (2019) reported different findings from this study; the Ca concentration was below WHO < 100 ppm, while Mg, Na, K, and Ni concentrations were recorded within the allowable limits set by WHO. The high values of Na were attributed to land-use practices [15].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The study by Wanjala et al (2019) reported different findings from this study; the Ca concentration was below WHO < 100 ppm, while Mg, Na, K, and Ni concentrations were recorded within the allowable limits set by WHO. The high values of Na were attributed to land-use practices [15].…”
Section: Discussioncontrasting
confidence: 87%
“…The study by Wanjala et al (2019) reported different findings from this study; the Ca concentration was below WHO < 100 ppm, while Mg, Na, K, and Ni concentrations were recorded within the allowable limits set by WHO. The high values of Na were attributed to land-use practices [15]. In agreement with this study, Ullah et al (2022) reported a similar finding, where polluted soil samples carried high potential toxic element concentrations, which were recorded above the permitted limits recommended by WHO [26].…”
Section: Discussioncontrasting
confidence: 87%
“…Economic activities (Table 1) conducted in the study areas include; drilling and mining, fishing, fish farming, horticulture, dairy farming and crop farming, industrial processing. The study areas were assigned codes as in Table 1 [8,9].…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…Locations of the sampling sites were identified using a GPS and the GPS readings recorded. Samples were transported to the laboratory for analysis [8,9].…”
Section: Samplingmentioning
confidence: 99%